2015
DOI: 10.1098/rspb.2015.2200
|View full text |Cite
|
Sign up to set email alerts
|

Macroevolutionary assembly of ant/plant symbioses:Pseudomyrmexants and their ant-housing plants in the Neotropics

Abstract: Symbioses include some of the clearest cases of coevolution, but their origin, loss or reassembly with different partners can rarely be inferred. Here we use ant/plant symbioses involving three plant clades to investigate the evolution of symbioses. We generated phylogenies for the big-eyed arboreal ants (Pseudomyrmecinae), including 72% of their 286 species, as well as for five of their plant host groups, in each case sampling more than 61% of the species. We show that the ant-housing Vachellia (Mimosoideae) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 56 publications
6
83
0
1
Order By: Relevance
“…Voucher information is reported in SI Appendix, Table S2. DNA extraction, PCR, sequencing, alignments, and phylogenetic analyses were performed as previously described (25) and are detailed in the SI Appendix, SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voucher information is reported in SI Appendix, Table S2. DNA extraction, PCR, sequencing, alignments, and phylogenetic analyses were performed as previously described (25) and are detailed in the SI Appendix, SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Here we use a species-rich and diverse ant/plant interaction system to study the ecological context under which breakdowns of symbiotic mutualisms have occurred on a geologic timescale. Ant/plant mutualisms are ubiquitous in tropical ecosystems and encompass a wide range of strategies (22)(23)(24)(25). In Australasia, the majority of ant-plants are epiphytes and appear to be primarily involved in trophic mutualisms rather than defense mutualisms (22,24).…”
mentioning
confidence: 99%
“…These ants were revised taxonomically more than twenty years ago, with the consequent recognition of ten species (Ward 1993). Since that time no additional species of obligate acacia-ants have been discovered, but recent studies have revealed that two undescribed species of generalist twig-nesting Pseudomyrmex are nested phylogenetically within the P. ferrugineus group Chomicki et al 2015;Ward & Branstetter, 2017). These two species are described herein and the definition of the P. ferrugineus group is updated to incorporate greater phenotypic variation in workers and queens.…”
Section: Introductionmentioning
confidence: 99%
“…1); such taxa are highlighted in bold font in the key. Species groups have been modified from those recognized in , to reflect more recent knowledge of phylogenetic relationships (Ward & Downie 2005;Chomicki et al 2015;Ward 2017). The key also includes taxonomically isolated species that are unplaced to a group.…”
Section: Provisional Key To Pseudomyrmex Species Groups Based On Thementioning
confidence: 99%
See 1 more Smart Citation